Reconciliation amidst a socio-economic crisis : a rhetorical critical reading of Nehemiah 5 against the background of the socio-economic situation in Judah during the reign of the Achaemenids - Turner, Edward Arthur (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 1998.